The General Attitudes towards Artificial Intelligence Scale (GAAIS): validation and psychometric properties analysis in the Italian context - Lavinia Cicero; Adriano Russo; Giovanni Di Stefano; Andrea Zammitti (BMC Psychology)
Abstract This two-study investigation aimed to assess the psychometric properties of the Italian version of the General Attitudes towards Artificial Intelligence Scale (GAAIS). In study 1 (N = 236 adults) confirmatory factor analysis (CFA) was conducted to examine the factorial structure of the scale. Study 2 (N = 177) assessed the concurrent and predictive validity of GAAIS. Concurrent validity was examined by correlating positive and negative attitude scores toward AI with another measure of attitude toward AI. Predictive validity was assessed by measuring the predictive ability of attitude on intention to use AI. The findings support the two-factor model, including for this Italian version of the scale consistent with the original one (Study 1). Moreover, positive attitudes towards artificial intelligence, as measured by the GAAIS positive factor, were positively correlated with general attitudes towards the use of AI, while the negative factor showed a significant negative correlation with the same general attitudes (Study 2). Then, the Italian version of the GAAIS can be considered as a valid tool for assessing people orientations towards artificial intelligence in the context analyzed, confirming the relevance of studying attitudes and its measurement towards artificial intelligence in different cultural contexts. This measure which relates to a strong psychosocial perspective, may support future research to deepen the understanding of the factors influencing attitudes towards AI as well as to develop more effective communication and training program interventions, being this a very crucial topic in actual society.